How alliteration enhances conceptual–attentional interactions in reading - Egan, C; Cristino, F; Payne, JS; Thierry, G; Jones, MW (Elsevier, 2019)
In linguistics, the relationship between phonological word form and meaning is mostly considered arbitrary. Why, then, do literary authors traditionally craft sound relationships between words? We set out to characterise how dynamic interactions between word form and meaning may account for this literary practice. Here, we show that alliteration influences both meaning integration and attentional engagement during reading. We presented participants with adjective-noun phrases, having manipulated semantic relatedness (congruent, incongruent) and form repetition (alliterating, non-alliterating) orthogonally, as in “dazzling-diamond”; “sparkling-diamond”; “dangerous-diamond”; and “creepy-diamond”. Using simultaneous recording of event-related brain potentials and pupil dilation (PD), we establish that, whilst semantic incongruency increased N400 amplitude as expected, it reduced PD, an index of attentional engagement. Second, alliteration affected semantic evaluation of word pairs, since it reduced N400 amplitude even in the case of unrelated items (e.g., “dangerous-diamond”). Third, alliteration specifically boosted attentional engagement for related words (e.g., “dazzling-diamond”), as shown by a sustained negative correlation between N400 amplitudes and PD change after the window of lexical integration. Thus, alliteration strategically arouses attention during reading and when comprehension is challenged, phonological information helps readers link concepts beyond the level of literal semantics. Overall, our findings provide a tentative mechanism for the empowering effect of sound repetition in literary constructs.